Ортез на колінний-гомілковостопний суглоби-стопу для динамічної розробки контрактур колінних суглобів у дітей - Баєв, П. О.; Півоваров, В. В.; Дацок, О. М. (ХНУРЕ, 2019)
In theses principles of static and dynamic stretching of contractures of knee joints are surveyed. It is shown, that the dynamic stretching is more effective than the static one because the technique of the static stretching of contractures assumes keeping a knee joint in a fixed position with constant effort, that in rather small period of time because of relaxation of a paretic muscle loses its efficiency. In this new design of knee - ankle - foot orthoses for dynamic stretching of contractures of a knee joint are represented with knee joints with a flat spiral spring.
Keywords: ортез; контрактури; динаміка